Estágio curricular supervisionado em Educação Física: aproximações com a teoria de Norbert Elias - Pereira da Silva Júnior, Arestides; Bássoli de Oliveira, Amauri Aparecido (Universidad de Costa Rica, 2018)
The aim of this assay is to discuss the influence of Supervised Teaching Practice on the initial training of Physical Education teachers based on the concept of configuration in Norbert Elias’ sociological theory. According to the configuration model suggested by the Elisian theory, the university and schools are complex nets of interdependent power relations. It highlights that teaching practice must be capable of promoting closer relations among elements that participate in the learning process during the initial training of future Physical Education teachers. The study presented the development of propositions to value and approximate teaching practice elements (college professors, school teachers and trainee students). The aim of these propositions is to enable instructions, knowledge exchange, relationships and reflections about pedagogical actions. Therefore, Supervised Teaching Practice is a dynamic, complex and extremely relevant part of the initial training of Physical Education teachers. However, discussions presented in the study and referenced by Norbert Elias’ theory reinforce the importance of configurations of, and relationships between, interdependent individuals. From the reflections and analyzes carried out, it was possible suggesting further field research with agents involved in the Supervised Teaching Practice in Physical Education, in order to assess such relations/incursions.